Large variations in all-cause and overdose mortality among >13,000 patients in and out of opioid maintenance treatment in different settings: a comparative registry linkage study - Gabrhelík, Roman; Hesse, Morten; Nechanská, Blanka; Handal, Marte; Mravčík, Viktor; Tjagvad, Christian; Thylstrup, Birgitte; Seid, Abdu Kedir; Bukten, Anne; Clausen, Thomas; Skurtveit, Svetlana (Frontiers in public health, 2023)
BACKGROUND: Opioid maintenance treatment (OMT) has the potential to reduce mortality rates substantially. We aimed to compare all-cause and overdose mortality among OMT patients while in or out of OMT in two different countries with different approaches to OMT. METHODS: Two nation-wide, registry-based cohorts were linked by using similar analytical strategies. These included 3,637 male and 1,580 female patients enrolled in OMT in Czechia (years 2000-2019), and 6,387 male and 2,078 female patients enrolled in OMT in Denmark (years 2007-2018). The direct standardization method using the European (EU-27 plus EFTA 2011-2030) Standard was employed to calculate age-standardized rate to weight for age. All-cause and overdose crude mortality rates (CMR) as number of deaths per 1,000 person years (PY) in and out of OMT were calculated for all patients. CMRs were stratified by sex and OMT medication modality (methadone, buprenorphine, and buprenorphine with naloxone). RESULTS: Age-standardized rate for OMT patients in Czechia and Denmark was 9.7/1,000 PY and 29.8/1,000 PY, respectively. In Czechia, the all-cause CMR was 4.3/1,000 PY in treatment and 10.8/1,000 PY out of treatment. The overdose CMR was 0.5/1,000 PY in treatment and 1.2/1,000 PY out of treatment. In Denmark, the all-cause CMR was 26.6/1,000 PY in treatment and 28.2/1,000 PY out of treatment and the overdose CMR was 7.3/1,000 PY in treatment and 7.0/1,000 PY out of treatment. CONCLUSION: Country-specific differences in mortality while in and out of OMT in Czechia and Denmark may be partly explained by different patient characteristics and treatment systems in the two countries. The findings contribute to the public health debate about OMT management and may be of interest to practitioners, policy and decision makers when balancing the safety and accessibility of OMT.
Keywords: Registries; buprenorphine with naloxone; registry-based study; Humans; poruchy spojené s užíváním opiátů; Buprenorphine; methadon; registrace; opiátová substituční terapie; Female; Drug Overdose; Opioid-Related Disorders; lidé; předávkování léky; Methadone; buprenorfin; ženské pohlaví; mortality; Male; opioid maintenance treatment; treatment outcomes; opioid agonist treatment; buprenorphine; mužské pohlaví; Opiate Substitution Treatment; methadone